Antecedent and Consequent Analysis of Career Development of Employees of PT. Mega Auto Central Finance (MACF) Serang Branch - Saefullah, Encep (LPPM Universitas Bina Bangsa, 2021)
This study aims to examine the antecedents and consequent analysis of career development. This research is a hypothesis testing with survey method. The population in this study were all employees of PT. Mega Auto Central Finance (MACF) Serang Branch was used as samples, namely as many as 64 employees. The analytical tool used to test the suitability of the proposed model and hypotheses using the regression method, the conclusion is that all four hypotheses are supported. The results show that career planning affects career development, career management involves career, career development impacts job satisfaction, and career development affects career commitment. PT. MACF Serang Branch should increasingly provide career opportunities to improve career planning and management, improving career development so that it is expected to create work commitment and high job satisfaction